Srijan I : Reflections of Teachers in an Orientation Programme - Kapur, Kirti (JOURNAL OF INDIAN EDUCATION, 2010)
Languages flourish in each others’ company today this is a proven reality. When we look back we find that some languages were considered more precious that others. The reason being, that these languages were associated with socio-political and economic power. While this can be traced to colonial times, the phenomenon continued till recent times. As a result barriers were created between Hindi and English, or other regional languages and English. In fact all languages as abstract systems or subsystems are equal. The science of language studies treats all language systems equally. And the myth that one language is superior to the other has been dispelled now. India is a multilingual country and thanks to our vibrant linguistic plurality, most of us are at least bilingual.